Digital holographic movie by using a point diffraction interferometer - Iemmi, Claudio César (2015)
A method to obtain a digital holographic movie by means of a point diffraction interferometer isdescribed. By using a parallel aligned liquid crystal wave plate of size 3 × 3 cm2, a phase shifting interferometrictechnique is implemented. The optical setup is able to operate at 10 frames∕s. Each frame can be digitally refocusedto reconstruct different planes of the three-dimensional (3-D) object. By changing the frame, the object canbe refocused in a different time. As an example, we show a movie which contains two objects that are separatedby 160 mm. The movie shows how, for a given time (a fixed hologram frame), we can focus at different planes(separated 0.1 mm) of the 3-D object, and by changing the frame the movement of the object can be observed.